Transformation and Development
VI, 154 p. 10 illus., 1 illus. in color.
Keywords: This open access book features various studies on democratization, transformation, political and economic development, and security issues in the Organization for Security and Cooperation in Europe (OSCE) geographical region and beyond. Written by experts and academics in the fields of human rights, security, transformation and development, particularly in post-soviet and communist countries, it examines the status quo of regime development in various member states of the OSCE; their economic, security and human rights performance; institutional reforms and transformations and the challenges that these countries and their societies face, including the USA, Canada, Germany, Macedonia, Russia, Turkey, Kazakhstan, Kyrgyzstan and Mongolia. This is the 2019 edition of this Compilation Series of the OSCE Academy. The OSCE works to promote Minority Protection, Security, Democratic Development and Human Rights guided by the Office for Democratic Institutions and Human Rights (ODIHR), and to enhance securitization and development policies in Eurasia, Europe, Central Asia and North America. Since being founded in 1993, theOSCE and its agencies and departments have attracted a wealth of academic research in various fields and disciplines, ranging from economic development and election monitoring to enhancing global principles of human rights and securitization. About the OSCE Academy in Bishkek: Founded in 2004, the Academy offers post-Doc research fellowships and runs two Master Degrees, one in Economic Governance and Development and one in Politics and Security in Central Asia. The Academy"s regular academic programs and conference contributes to developing human professional capital in the sectors of particular importance for Central Asian states and societies. The Academy's graduates and visiting researchers contribute to economic development, governance and policy-making in Central Asia and beyond the OSCE region. Website: Link .